(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This article analyses various approaches to teaching linear regression using Python and Excel. The inductive and deductive methods, as well as problem-based learning, are examined. Examples of using the scikit-learn library or Excel functionalities for building linear regression models are described. Practical tasks are presented to support the understanding of regression analysis concepts.